1996
DOI: 10.1046/j.1365-2141.1996.d01-1493.x
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Blackfan anaemia: differential pattern of in vitro progenitor response to macrophage inflammatory protein 1‐alpha

Abstract: The congenital disorder of erythropoiesis Diamond Blackfan anaemia (DBA) exhibits a defect in the stem/progenitor cell compartment, located at the erythroid progenitor level (CFU-GEMM, BFU-E, CFU-E). Treatment of DBA with interleukin-3 (IL-3) has had limited effect, despite in vitro studies suggesting that progenitor cells were capable of responding to IL-3. Whether IL-3 is not reaching the appropriate defective target cell, the cells cannot respond, or the marrow humoral inhibitory system is overriding it, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Separate experiments in stem cells harvested from the bone marrow of haematologically normal volunteers revealed that optimal colony formation was achieved using a SCF, IL-3, GM -CSF and EPO cocktail, consequently, all short-term cultures utilised this combination (McGuckin et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate experiments in stem cells harvested from the bone marrow of haematologically normal volunteers revealed that optimal colony formation was achieved using a SCF, IL-3, GM -CSF and EPO cocktail, consequently, all short-term cultures utilised this combination (McGuckin et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…A hallmark of CML is the expansion of immature progenitor cells of the myeloid lineage in the bone marrow compartment, so that the majority of peripheral circulating CD34 + cells from CML patients are myeloid (Fialkow et al, 1977). PSCs were harvested from suspension cultures, washed and plated on semi-solid methylcellulose plates supplemented with a cocktail of GFs conducive to erythroid colony formation (McGuckin et al, 1996). Results were similar to those of Thiesing et al (2000), and showed that although there was a large number of cells seen on the culture plates, most lacked clonogenic capability since only a small number of colonies were seen.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
“…In vitro a variable response to cytokines such as IL-3, SCF, GM-CSF and human recombinant erythropoietin has been demonstrated. 4,5 For patients who remain steroid-resistant the therapeutic options include regular transfusion therapy with chelation Correspondence: Dr RF Wynn, Royal Manchester Children's Hospital, Manchester, M27 4HA, UK Received 18 January 1999; accepted 13 May 1999 and stem cell transplantation. We report a case of failure of BMT to correct DBA, despite adequate engraftment.…”
mentioning
confidence: 99%
“…Blood chemistry studies showed raised levels of vitamin B12 ( I 340 pgldL), serum Fe (1 85 pg/dL), serum Fe and total iron-binding capacity (TIBC) ratio (185/197), and serum ferritin (514.5 ng/mL). Hb F was 19…”
mentioning
confidence: 99%